2016
DOI: 10.1111/jfpp.12739
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Kinetics of Acrylamide Formation in Banana Chips

Abstract: This study was undertaken to study acrylamide formation during deep-fat frying of ripe and unripe banana chips at 150, 170 and 190C up to 360 s. The moisture content, oil content, color and texture of the fried chips were also monitored during frying. The acrylamide formation was higher in ripe banana chips than unripe banana chips at all temperatures of frying. Acrylamide formation followed first order kinetics with increase in rate constant (k) value from 0.023 to 0.026 for ripe, and from 0.023 to 0.029 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hence, combined treatment was implemented for the investigation of acrylamide reduction (Pedreschi et al, 2010). The activation required during the Maillard reaction was calculated from the Arrhenius plot and was found to be 471.75 J mol À1 (Mulla et al, 2017).…”
Section: Combined Effect Of Additives and Asparaginase On Acrylamide mentioning
confidence: 99%
“…Hence, combined treatment was implemented for the investigation of acrylamide reduction (Pedreschi et al, 2010). The activation required during the Maillard reaction was calculated from the Arrhenius plot and was found to be 471.75 J mol À1 (Mulla et al, 2017).…”
Section: Combined Effect Of Additives and Asparaginase On Acrylamide mentioning
confidence: 99%
“…Many studies have focused on AA formation routes to inhibit AA: reducing or scavenging precursor substances, optimising processing conditions, adding additives (Morales et al ., ; Mulla et al ., ; Nguyen et al ., ). Nguyen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Mulla et al . () indicated that shorter frying time accompanied by lower temperatures would reduce AA formation in potato chips. However, these methods may affect the colour, taste and texture of food to a certain degree (Morales et al ., ), adding additives to inhibit AA formation is a preferable solution to reduce AA formation while maintaining the original sensory qualities.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of deep‐fried chips and snack products made from sources other than potato are popular all over the world, to name a few—plantain, sweet potato, tapioca, jackfruit, etc. Very few studies have been published on acrylamide content of these products and on the mitigation strategies (Daniali, Jinap, Hanifah, & Hajeb, ; Mulla, Annapure, Bharadwaj, & Singhal, ). The authors have done a preliminary survey to find out the acrylamide content of some of the deep‐fried chips from India (Shamla & Nisha, ) and reported considerable amount of acrylamide in plantain and jackfruit chips.…”
Section: Introductionmentioning
confidence: 99%